Comparative study of different grains for spawn production of pleurotus florida - Prajapati, Priyanka J.; Shinde, Manisha; Nakrani, B. R. (Mushroom Research, 2024)
The present research was conducted to evaluate the growth and development of oyster mushrooms (P. florida) on five different grains (viz., wheat, maize, bajara, sorghum and mustard) at the Polytechnic in Agriculture, Sardarkrushinagar Dantiwada Agricultural University, Deesa (Gujarat) during 2022-23. The observations on the initiation of mycelium on grain spawn and days for complete colonization of mycelium on grain spawn were recorded. The results showed that the minimum (4 days) days required for initiation of mycelium run of P. florida in the treatment of sorghum and bajra grains. While maximum (13 days) days required in mustard grain. The result showed that early initiation of mycelial run was found in bajara and sorghum grains (2 days), while complete colonization of P. florida was observed at 7 and 8 days in bajara and sorghum grains.